Changes in Soil Chemical Properties of Organic Paddy Field with Azolla Application - Jauhari Syamsiyah; Bambang Hendro Sunarminto; Mujiyo Mujiyo (Faculty of Agriculture, Universitas Sebelas Maret, 2016)
The use of high organic fertilizer in the organic farming system is one of the obstacles in the implementation of organic farming in Indonesia. It is necessary to find alternative materials to substitute or meet the shortage of existing organic fertilizer. This study aims to determine the effect of Azolla (Azolla mycrophylla. L) on some soil chemical properties on organic paddy field. The The field experiments used factorial complete randomized block design of three factors, namely Azolla (0 and 2 tons / ha), Manure (0 and 10 tons / ha) and Rice Varieties ( Mira1, Mentik Wangi and Merah Putih), with three times replication. Azolla 2 tons / ha is able to increase soil total N 18%; available P 87,5 %; organic C 3,78% CEC 8,03 % and soil pH 1,00%; compared to control (without Azolla). Compared with manure 10 tonss / ha, giving Azolla 2 tonss / ha was able to increase only on soil available P about 50 %, but lower on soil total N, organic C, CEC and soil pH 1,9% ; 9,27% ; 9,40% and 0,67%. Azolla can be used as a substitute or complement of manure on organic paddy field.